Neuroprotective Effect of PBCA Nanoparticles Delivering pEGFP-BDNF in a Mouse Model of Intracerebral Hemorrhage - Xue Lai; Yu Xiong; Xing Guo; Chunbo Chen (Journal of Integrative Neuroscience)
Objectives: Polybutylcyanoacrylate (PBCA) nanoparticles (NPs) were prepared by emulsion polymerization and loaded with an enhanced green fluorescent protein plasmid (pEGFP) encoding human brain-derived neurotrophic factor (BDNF). This study investigated the potential effects of PBCA-pEGFP-BDNF NPs for the treatment of experimental cerebral hemorrhage mouse model animals. Methods: Eight-week-old male mice (30 ± 5 g) were randomly divided into four groups (sham, intracerebral hemorrhage (ICH), ICH+PBCA NPs, and ICH+ PBCA-pEGFP-BDNF NPs; n = 14). An ICH model was constructed by right striatum injection of bacterial collagenase VII. Neurological function was evaluated by modified Garcia score after treatment of ICH mice with PBCA-pEGFP-BDNF NPs. The area of cerebral hematoma was measured and the water content of brain tissues was calculated by the wet/dry ratio method. Finally, immunofluorescence staining was used to detect neuron-specific nuclear protein (NeuN) positive cells around hematomas. Enzyme-linked immunosorbent assay (ELISA), real-time quantitative polymerase chain reaction (qPCR), and western blot were used to detect inflammatory BDNF, nuclear factor kappa-B (NF-κB), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and either interleukin-1 beta (IL-1β) mRNA or protein levels. Results: Treatment with PBCA-pEGFP-BDNF NPs significantly improved neurological function and reduced acute brain edema and neuroinflammation in the mouse model of ICH. qPCR, ELISA, and western blot results showed that PBCA-pEGFP-BDNF NPs increased BDNF expression, inhibited NF-κB signaling pathway activity, and decreased the levels of inflammatory factors (IL-6, TNF-α, IL-1β) when compared with the recombinant plasmid pEGFP-BDNF. Conclusion: PBCA-pEGFP-BDNF NPs improves neurological function in experimental ICH mice at least in part related to increased BDNF expression and decreased p65 NF-κB signaling axis activation, suggesting that PBCA NPs might be a suitable pEGFP-BDNF-carrying delivery system for ICH treatment.